Private Chinese Investment in Africa : Myths and Realities - Shen, Xiaofang (World Bank, Washington, DC, 2013)
Private Chinese outbound investment, not as well-known as government-led investment, offers special opportunities and challenges for Africa today. The significance of Chinese private-sector investment is already visible in the burgeoning manufacturing sector in some parts of Africa, and the trend will continue to grow in the near future. The underlying force behind this trend is the increased pressure of industrial restructuring in coastal China, a force that drives some labor-intensive firms to relocate to other parts of the developing world, including Africa. African host country governments can respond to this phenomenon with proactive development policies and strategies to maximize private Chinese investment for the benefit of their own economies.